In pursuit of an African traditional dance : an afrocentric historical study of Buum Oku Dance Yaounde - Jing, Thomas (Langaa RPCIG, 2022)
"Africa is rich in (neo) traditional dances; yet, not much exists in the form of written literature on the subject. Even worse, existing documents date back to the colonial period and are often disparaging. Dance to Africans is what martial arts are to Asians. Embedded in them are some of the solutions to many of the problems wracking the African diaspora: gang violence, drug addiction, and high school dropout rates, etc. When Guinea's Ballets Africains first bursts on the international scene in the late fifties and sixties, the black revolution in the US was in full swing. The troupe's emancipatory message enkindled in African Americans a new sense of cultural pride and a return to their African roots. For once, dance became something else other than the ballet. With that burst of enthusiasm came the need to introduce African dances in the academia. Most of the research, however, focused mainly on dances which use drums (djembe). Departing from that tradition, in this detailed and richly choreographed ethnography on the Buum Oku Dance Yaounde, Thomas Jing's investigation into a xylophone-based dance opens up new research avenues and exposes the challenges involved. An Afrocentric theoretical framework to the research counters imperialist notions of African dances, thus setting them up as a tool for emancipation"--